"I am sick and tired of this congestion": Perceptions of Sanandaj inhabitants on the family mental health impacts of urban traffic jam. (September 2019) - Nadrian, Haidar; Taghdisi, Mohammad Hossein; Pouyesh, Kowsar; Khazaee-Pool, Maryam; Babazadeh, Towhid
Abstract: Introduction: Traffic and transportation are important determinants in the spectrum of social, economic and environmental factors outside the health sector which has been known to impact public health. The aim of this study was to explore the perceptions of inhabitants and key informants on the impacts of Sanandaj urban traffic jam (UTJ) on family mental health. Methods: It was a qualitative study with semi-structured interviews. Applying purposeful sampling, 30 residents/key informants were invited to participate in the study. Data collection was conducted through 4 Focus Group Discussions (FGDs) with 22 residents and in-depth interviews with 8 key informants. To conduct analysis, interpretative thematic analysis was used. MAXQDA10 was applied for the purpose of data management. Results: Based on the participants' perceptions, Sanandaj urban traffic jam had a wide range of impacts on family mental health, and, consequently, " life quality is diminished" . Depending on the issue participants were reffering to, the health impacts were grouped into two main themes: (i) impacts on families in general population, including "trigerring stress and anxiety", "reducing tolerance threshold", "trigerring family quarrel/squabble", "regreting at traffic accidents" and "annoying about and bored with air/noise pollution"; and (ii) impacts on the families of inner-city drivers, including "lack of family cohesion", "dissatisfaction within family", "disturbance in family progression", and "frowning in concentration". Conclusion: The UTJ in Sanandaj has led to diminished mental health and weakend life quality among families of both general population and inner-city drivers. Our results may help public health practitioners and urban traffic and transportation (UTT) stakeholders in finding a better understanding on potential health impacts of UTJs. In developing countries, like Iran, there is great need to health-oriented policymaking while developing UTT plans and projects. Highlights: Discusses how urban traffic jams weaken family mental health. Turns the spotlight on an often-neglected group mainly-affected by urban traffic jam: inner-city drivers. Discribes how urban traffic jams underpin quality of life. Highlights the role of health impact assessments prior to implementing the urban traffic an transportation plans.